Valuable experience: How internships affect university graduates' income - Thomas Bolli; Katherine Caves; Maria Esther Oswald-Egg (ETH Zurich, KOF Swiss Economic Institute, 2019)
This paper analyzes whether and how attending an internship during tertiary education affects income. We address endogeneity with an IV approach that exploits information regarding whether the internship was a mandatory component of the study. We further address selection into programs with mandatory internship by using the share of mandatory internships at the closest university, exploiting the low mobility of Swiss students. The results suggest that doing an internship increases income. In contrast to the literature on internships we find that the effect mainly works by increasing human capital rather than through signaling, and mainly works through general rather than firm- or field-specific human capital.
Keywords: I23; J01; J31; 330; Internship; Income; Human capital; Signaling; Soft skills; Experience